A global call for talaromycosis to be recognised as a neglected tropical disease. Issue 11 (November 2021) - Narayanasamy, Shanti; Dat, Vu Quoc; Thanh, Nguyen Tat; Ly, Vo Trieu; Chan, Jasper Fuk-Woo; Yuen, Kwok-Yung; Ning, Chuanyi; Liang, Hao; Li, Linghua; Chowdhary, Anuradha; Youngchim, Sirida; Supparatpinyo, Khuanchai; et al.
Summary: Talaromycosis (penicilliosis) is an invasive mycosis that is endemic in tropical and subtropical Asia. Talaromycosis primarily affects individuals with advanced HIV disease and other immunosuppressive conditions, and the disease disproportionally affects people in low-income and middle-income countries, particularly agricultural workers in rural areas during their most economically productive years. Approximately 17 300 talaromycosis cases and 4900 associated deaths occur annually. Talaromycosis is highly associated with the tropical monsoon season, when flooding and cyclones can exacerbate the poverty-inducing potential of the disease. Talaromycosis can present as localised or disseminated disease, the latter causing cutaneous lesions that are disfiguring and stigmatising. Despite up to a third of diagnosed cases resulting in death, talaromycosis has received little attention and investment from regional and global funders, policy makers, researchers, and industry. Diagnostic and treatment modalities remain extremely insufficient, however control of talaromycosis is feasible with known public health strategies. This Viewpoint is a global call for talaromycosis to be recognised as a neglected tropical disease to alleviate its impact on susceptible populations.